Memahami Komunikasi Antarpribadi dalam Perkawinan Campuran Pasangan Suami Istri Beda Negara Indonesia Italia - Ani, Ari Murti (Universitas Semarang, 2015)
The paper aims to understand and describe the understanding of interpersonal communication is done by married couples of different countries in the intermarriage. The theoretical basis of this research is interactionism symbolic by George Herbert mead (1934 ) describes the thinking is the interaction that occurs in an individual, how language is essential for the formation of human characteristics which consist of Mind, Self and Society. The process of symbolic form of messages and symbols. Based on research that has been done, it can be concluded that the verbal and nonverbal communication is a form of symbolic interaction that happens to couples from different countries and the adjustment effort in communicating basically used by mutual consent.